Dynamic control of a 10 MW solar-autothermal hybrid biomass gasifier for round-the-clock processing with stable syngas production - Curcio, Axel; Rodat, Sylvain; Vuillerme, Valéry; Abanades, Stéphane (Energy conversion and management. X, 2025)
•An upscaled hybrid biomass gasifier was modelled featuring solar and autothermal heating.•Dynamic simulation and control were achieved for continuous and constant fuel production.•Daily to yearly gasification performance results were determined at 10 MW gasifier scale.•Temperature and syngas production targets were stabilized via dynamic control.•The yearly solar heat share decreased with increasing H2 + CO production objectives. This study tackles the theoretical controllability of a hybrid solar-autothermal biomass gasifier, subject to dynamic variations of the solar power input, for round-the-clock operation. An industrial-scaled spouted bed reactor is considered, which can ensure the continuous conversion of 2 to 3 t/h of woody biomass particles. Insufficient solar power is dynamically counterbalanced by in situ oxy-combustion, to maintain the reaction temperature at 1200 K and the total H2 + CO flowrate production at 1000 NL/s. A Model Predictive Control (MPC) algorithm is thus implemented, and the feasibility of hybridized operation is demonstrated on a second-per-second basis. Daily and yearly performance results are achieved to discuss the relevance of several model assumptions and design choices, and a sensitivity analysis is proposed. In the region of Targasonne (French Pyrenees), hybridized gasification enables reducing biomass and O2 consumptions by 6.2 % and 19.5 %, respectively, as compared with autothermal gasification for the same gas flowrate production. The yearly solar heat share reaches 22 %, while a 7.2 % dumping of the solar heat available is necessary to avoid over-heating. Within this scope, higher H2 + CO production rates can only be achieved at the cost of lower solar heat shares but lower dumping rates, thus better utilization of the available solar resource. The feasibility of dynamic control of a solar-autothermal biomass gasifier was successfully demonstrated for the determination of annual process performance with reasonable computational costs, paving the way to stable and controllable solar gasification process operation.